Mechanisms of integration and cooperation between Ecuador, Peru, and Colombia: Institutional evolution, results, and perspectives - Cisneros-Corrales, Edison Patricio (2026)
This article analyzes the cooperation and integration mechanisms between Ecuador, Peru, and Colombia, with the aim of identifying results, demonstrating their importance in strengthening relations, and demonstrating their future prospects. A qualitative methodology based on documentary analysis is used. The article is divided into four sections: the context of regional integration, past and present cooperation mechanisms, technical cooperation mechanisms, and finally, conclusions and recommendations. It concludes that the flexibility and adaptability of thebinational mechanisms have been key to their success, although factors such as political will and inter-institutional coordination can affect their effectiveness. It is suggested that their dynamic and up-to-date nature be maintained.